Actual and perceived expertise : the role of social comparison in the mastery of right and left recognition in novice-expert dyads - Grossen Peretti, Michèle; Iannaccone, Antonio; Liengme Bessire, Marie-Jeanne; Perret-Clermont, Anne-Nelly (My University, 1996)
In line with the post-Piagetian strand, this article presents a study exploring the role of social comparison with regard to the individual benefits children might gain after a peer interaction session. 52 7-8 year-old children participated in the expenment. The task involved the recognition of right and left on one's own or another's body. The experimental design was a classical pretest-post-test design including an additional session in which the perceptions each child had of hisker own level of expertise and that of the partner were manipulated just before an interaction session between an expert and a novice. The expenmental manipulation consisted of inducing either an unequal (condition 1) or an equal (condition 2) perception of the expertise. Results showed that condition 2 brings about more progress among the novices than condition 1 in the substests which are the most easy to solve. Additional results conceming some characteristics of the interaction session are also reported.